The Evaluation of Policies and Success Factors of E-Government Parking Tax Implementation in Capital Region of Jakarta - Evi Ratna Wulandari; Roy Valiant Salomo (Universitas Padjadjaran, 2021)
The implementing of parking tax e-government policy in DKI Jakarta has been going on for approximately 7 (seven) years. In its implementation, there are many advantages and disadvantages that have an impact on the performance targets that have been set. This study aims to analyze and evaluate the policies and factors that determine the success of implementing the parking tax e-government in DKI Jakarta. This study uses the post-positivism method which uses theory as a reference in understanding research problems. The evaluation results of this study indicate; (1) the benefits of the online system have not significantly helped tax officers in monitoring compliance with taxpayers because only 3.37% of taxpayers routinely report their business transactions; (2) e-government applications have not been able to integrate Bapenda, DPMPTSP and UP Parking; (3) sanctions have not been applied firmly; (4) the business license revocation sanction is not in accordance with the higher tax regulations; and (5) the obligation to report business transactions online has not been optimally applied to all parking taxpayers, because there is still unpreparedness both in terms of taxpayers and electronic device support.